lg(x-1)+lg(6x-5)=2

Simple and best practice solution for lg(x-1)+lg(6x-5)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for lg(x-1)+lg(6x-5)=2 equation:


Simplifying
lg(x + -1) + lg(6x + -5) = 2

Reorder the terms:
gl(-1 + x) + lg(6x + -5) = 2
(-1 * gl + x * gl) + lg(6x + -5) = 2
(-1gl + glx) + lg(6x + -5) = 2

Reorder the terms:
-1gl + glx + gl(-5 + 6x) = 2
-1gl + glx + (-5 * gl + 6x * gl) = 2
-1gl + glx + (-5gl + 6glx) = 2

Reorder the terms:
-1gl + -5gl + glx + 6glx = 2

Combine like terms: -1gl + -5gl = -6gl
-6gl + glx + 6glx = 2

Combine like terms: glx + 6glx = 7glx
-6gl + 7glx = 2

Solving
-6gl + 7glx = 2

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Reorder the terms:
-2 + -6gl + 7glx = 2 + -2

Combine like terms: 2 + -2 = 0
-2 + -6gl + 7glx = 0

The solution to this equation could not be determined.

See similar equations:

| 0=x^2+(2k+1)x-(2k-1) | | 8(x-1)=12+3x | | 6*x*9=8 | | 2x+4=+9 | | 2x-13=x+14 | | 1/4x-18=1/2x-6 | | 3x^2+x-310=0 | | 3x(2+8)= | | x-8.2=-4.8 | | 17500x=600000 | | 125000+65x=175.00x | | x=147000000(1.15) | | (x^2y-y^2)dx-x^3dy=0 | | i=(300)(0.11)(2) | | 175.00+2.00x=175.00+3.00x | | p=2(31)+2(100) | | 6ln(x-6)+3=4 | | 6p+2=7+5p | | 1.930236x=1494 | | -12+9x+3y=0 | | x+.18x=634 | | 2(34)+2(90)= | | x+.18x=600 | | x-.18x=600 | | x(x-1)=100 | | 1z+1x= | | 1z+2008238742x= | | 1a+2837438x=a+s | | 5+4a=5-6a | | 4.8x-4= | | -4n+2n+7=1 | | -4n+2n+7= |

Equations solver categories